اثر الدعم الاجتماعي في تعزيز الصحة النفسية لدى العاملين في القطاع الصحي : دراسة ميدانية - جدوح, صادق جعفر حسن سلمان (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
has lived since the beginning, the creation of the universe, for thousands of years, searching for stability and security, searching for comfort that would make him feel balanced and reassured. Since that time, he has been seeking reassurance for himself and his children, and seeking to ease the burden of life on him. As life became more complex and its demands and needs multiplied, The pressure on him to meet these needs increased. Through what theorists have sought about support systems and their impact on the psychological health of the individual and society, social support includes an integrated pattern of continuous or few relationships that play a major role in maintaining the unity of the soul and body of the person throughout his life, and it clarifies that social support for the person Provide him with social supplies. Psychological, especially in light of difficult events, in order to preserve the individual’s mental and psychological health, and from here the objectives of the research and what they aspire to have become clear. The research aims to identify: 1- Social support for health sector workers. 2- Identifying the aspects that need to increase social support in enhancing the mental health of health sector workers. 3- Identify the statistical differences in social support for workers in the health sector according to the gender variable (male and female workers.( To achieve the objectives of the research, the researcher built a social support scale, which consists of (21) items and consists of four domains. He extracted its validity and reliability and applied it to a sample of (200) male and female workers in the health sector who were selected by a random stratified method. The researcher used methods The appropriate statistics for his research, using the Spss statistical package, and the tool was presented to the arbitrators and the tool was applied to the sample members. The results showed that the workers in the primary health care sector in the city of Tal Afar. they enjoy acceptable level of social support. It also identified a number of aspects from the items of the scale that represent aspects that need To enhance workers to raise their level of social support. It also showed that there are differences in the level of social support according to the gender variable and in favour of males compared to females. In light of the research results, the researcher developed a number of recommendations and proposals. The researcher reached the following results: Health sector workers enjoy social support. There are also statistically significant differences in the level of social support in the gender variable (males - females) in favour of males. Social support has a major role in psychological support for workers in the health sector, and achieves success for them in completing their job tasks in the work environment in the health sector. To complement the aspects related to the research, the researcher has developed a number of proposals and recommendations.